2022
DOI: 10.1136/bmjsem-2021-001265
|View full text |Cite
|
Sign up to set email alerts
|

Behind the athletic body: a clinical interview study of identification of eating disorder symptoms and diagnoses in elite athletes

Abstract: Eating disorders are more prevalent in athletes than in the general population and may have severe consequences for sports performance and health. Identifying symptoms can be difficult in athletes because restrictive eating and slim body images are often idealised in a sports setting. The Eating Disorders Examination Questionnaire (EDE-Q) and the SCOFF (Sick, Control, One stone, Fat and Food) questionnaire (SCOFF) are widely used generic instruments to identify symptoms of eating disorders. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…These are underlined by qualitative work from Lichtenstein et al, which revealed psychosocial pressures from a cyclist's family: "My father says that cyclists starve themselves. He says I shouldn't weigh more than 60 kg" [34]. Such findings raise concerns for athlete wellbeing, as do data from our review showing extreme weightloss practices, like fasting [32], supplement use [32,33,35], and purging [33,35].…”
Section: Eating Disordersmentioning
confidence: 87%
See 3 more Smart Citations
“…These are underlined by qualitative work from Lichtenstein et al, which revealed psychosocial pressures from a cyclist's family: "My father says that cyclists starve themselves. He says I shouldn't weigh more than 60 kg" [34]. Such findings raise concerns for athlete wellbeing, as do data from our review showing extreme weightloss practices, like fasting [32], supplement use [32,33,35], and purging [33,35].…”
Section: Eating Disordersmentioning
confidence: 87%
“…The papers in our results discuss mental health issues or evidence of psychiatric symptomatology per ICD-11 classifications. These included ED in eight studies [30][31][32][33][34][35][36][37], depression in five [30,32,[38][39][40], anxiety disorder in two [38,40], sleep wake disorders in two [38,41], SUD in two [30,38], and ADHD in one [42]. However, with the exception of three instances of secondary analysis [36,39,42] and one cohort of n = 122 cyclists [35], primary investigations had relatively small sample sizes; this is not atypical since practical and logistical challenges can occur when recruiting elite-level or highperformance athletes [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BMI trends in our data and evidence of harmful behaviours and attitudes in cycling suggest that multifactorial regulatory measures may be required. To that end, screening tools can help identify ED symptomatology in various sporting disciplines [7,49], which could prove bene cial if implemented within elite-level cycling. Nonetheless, as Ribel et al discuss, self-reported instruments might not necessarily be reliable because deleterious weightmanagement practices may be normalised [11] and diagnostic tools would need to be adapted to account for inherent gender biases [50].…”
Section: Towards Increased Regulatory Attention and Interventionsmentioning
confidence: 99%